2017
DOI: 10.1002/ajmg.a.38139
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phenotypic and network analysis of 1q44 microdeletion for microcephaly

Abstract: As genome wide techniques become more common, an increasing proportion of patients with intellectual disability (ID) are found to have genetic defects allowing genotype-phenotype correlations. Previously, AKT3 deletion was suggested to be responsible for microcephaly in patients with 1q43-q44 deletion syndrome, but this does not correspond to all cases. We report a case of a de novo 1q44 deletion in an 8-year-old boy with microcephaly in whom AKT3 is not deleted. We used a systematic review of the literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…However, in the genetic study of our patient, an alteration was found in the SMYD3 and NLRP3 genes. These genes are postulated as possible causes of microcephaly in another publication 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the genetic study of our patient, an alteration was found in the SMYD3 and NLRP3 genes. These genes are postulated as possible causes of microcephaly in another publication 2…”
Section: Discussionmentioning
confidence: 99%
“…​In 90% of the cases, they present alterations in the central nervous system, the most common is the corpus callosum’s agenesis and the less frequent, hydrocephalus and delay in myelinisation 3 5. Seizures, appearing between 6 months and 3 years, have been reported in 85% 2 6 7…”
Section: Discussionmentioning
confidence: 99%
“…All six genes shared the same cyto-band: 1q44; therefore, we suggest this location to be further investigated for a relation with HCC in all patients in general (since 9.31% of all patients had an alteration in this cyto-band) and children in specific. 1q44 has been linked in other studies to abnormalities like microcephaly, seizures, and other diseases [ 41 ]. More genes were found in the elderly group (299 genes).…”
Section: Discussionmentioning
confidence: 99%
“…Duplication involving AKT3 can cause macrocephaly [ 33 ]. A report on a boy who had a 4.1 Mb terminal deletion in 1q44 stated that the patient had MIC, the deletion encompasses the HNRNPU gene but not AKT3 [ 34 ]. A similar finding was reported on another patient who had a de novo 1.2 Mb interstitial deletion and had MIC, the deletion encompasses ZBTB18 and HNRNPU genes but not AKT3 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also found the same abnormalities in three patients out of four who had ZBTB18 mutation [ 11 ]. This is not the case in all the patients with deletion or mutation in ZBTB18 gene as some had a normal corpus callosum, and the authors have related this to the incomplete penetrance of the gene [ 34 ].…”
Section: Discussionmentioning
confidence: 99%